2022
DOI: 10.1111/nyas.14936
|View full text |Cite
|
Sign up to set email alerts
|

Breeding and adoption of biofortified crops and their nutritional impact on human health

Abstract: Micronutrient malnutrition has affected over two billion people worldwide and continues to be a health risk. A growing human population, poverty, and the prevalence of low dietary diversity are jointly responsible for malnutrition, particularly in developing nations. Inadequate bioavailability of key micronutrients, such as iron (Fe), zinc (Zn), and vitamin A, can be improved through agronomic and/or genetic interventions.The Consultative Group on International Agricultural Research prioritizes developing biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 125 publications
0
5
0
Order By: Relevance
“…29 In rice, grain Zn concentration could be significantly increased with the use of alternate wetting and drying as a water management strategy, which improves the redox status of the soil and plant availability of soil Zn. 30 Given the wheat and rice grain Zn concentrations used in this study (Table 2) and recently published overview of released wheat and rice varieties with enhanced grain Zn levels, 47 there is a good potential for also introducing to farmers in China varieties that reach the proposed breeding targets. 10 This will require some more breeding effort to introduce this grain Zn potential into lines fitted to the different agro-ecologies and market demands with which farmers are faced.…”
Section: Discussionmentioning
confidence: 99%
“…29 In rice, grain Zn concentration could be significantly increased with the use of alternate wetting and drying as a water management strategy, which improves the redox status of the soil and plant availability of soil Zn. 30 Given the wheat and rice grain Zn concentrations used in this study (Table 2) and recently published overview of released wheat and rice varieties with enhanced grain Zn levels, 47 there is a good potential for also introducing to farmers in China varieties that reach the proposed breeding targets. 10 This will require some more breeding effort to introduce this grain Zn potential into lines fitted to the different agro-ecologies and market demands with which farmers are faced.…”
Section: Discussionmentioning
confidence: 99%
“…Large populations worldwide suffer from micronutrient malnutrition, inflicting severe socio-economic losses which creates a global concern [40]. The deficiency of iron and zinc can be effectively addressed by developing low PA maize cultivars possessing mutant lpa1-1 allele [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing production of crops with bioavailable micronutrients: a solution to reduce global malnutrition Malnutrition refers to diets that do not contain the proper amounts of nutrients, while hidden hunger refers to micronutrient deficiencies and affects almost one third of world population (Dwivedi et al, 2023). Recent scientific advances have focused on biotechnology and agronomic practices that may improve the nutritional quality of crops and contribute to combating malnutrition and ensure food security (Kumar et al, 2023;Singh Dhaliwal et al, 2023;.…”
Section: Editorial On the Research Topicmentioning
confidence: 99%
“…
Editorial on the Research TopicIncreasing production of crops with bioavailable micronutrients: a solution to reduce global malnutrition Malnutrition refers to diets that do not contain the proper amounts of nutrients, while hidden hunger refers to micronutrient deficiencies and affects almost one third of world population (Dwivedi et al, 2023). Recent scientific advances have focused on biotechnology and agronomic practices that may improve the nutritional quality of crops and contribute to combating malnutrition and ensure food security (Kumar et al, 2023;Singh Dhaliwal et al, 2023;.This Research Topic compiles innovative research studies and review reports that gather up the most up-to-date information regarding the use of agronomic techniques that can be applied to various crops and result in higher bioavailability of micronutrients without compromising yield and quality of the final product.Yang et al investigated the selenium (Se) uptake and distribution dynamics in rice plants via Algal Polysaccharides-Selenium Nanoparticles (APS-SeNPs). Their hydroponic study, anchored in the Michaelis-Menten equation, revealed a notable Vmax of 13.54 mg g −1 root dry weight/hour for APS-SeNPs -7.69 and 2.23 times higher than selenite and selenate treatments, respectively.
…”
mentioning
confidence: 99%